REGULATION CONCERNING SEAFARER ON MARITIME LABOR CONVENTION 2006 - Thio Haikal Anugerah (Faculty of Law Universitas Lampung, 2019)
The enactment of Law No. 15 of 2016 which regulates seafarers results in the adoption of the convention in Indonesia. The adoption of the MLC by the ILO was carried out with the aim of protecting seafarers and the shipping industry. The problem is, Indonesia actually has a regulation on Maritime Affairs, namely in Government Regulation Number 7 of 2000. Then, in terms of whether the State of Indonesia then feels the need to participate in ratifying the MLC. This then attracts the authors to examine the related arrangements regarding seafarers contained in MLC convention. Therefore, the formulation of the problem in this study is how is the regulation about Seafarers in the Maritime Labor Convention, 2006?The problem approach used in this study is the statute approach. This study uses secondary data consisting of primary, secondary, and tertiary legal materials. Data analysis was carried out qualitatively. The results of the study show that the framework of the Maritime Labor Convention or MLC is composed of three parts, namely Articles, Regulation and Codes. The arrangements for seafarers in the MLC consist of six parts, namely: seafarers’ rights; minimum requirements to work for seafarers; working conditions; accommodation, recreational facilities, food and catering; health protection, medical care, welfare and social security; compliance and enforcement.